2018
DOI: 10.4209/aaqr.2017.11.0463
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Impact of African Dust Storms on the Presence of Enteric Viruses in the Atmosphere in Tenerife, Spain

Abstract: 20Airborne viruses and their relation to dust storms, as a possible route for dispersion, has 21 not been widely investigated. There are, however, studies that have described airborne

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 68 publications
0
13
0
Order By: Relevance
“…PCR is used to amplify the DNA region of interest prior to the traditional Sanger sequencing. Many bioaerosol studies use Sanger sequencing to identify an organism in terms of its individual genera/species by comparing its DNA with sequences available on online databases, such as the National Center for Biotechnology Information (NCBI) (Després et al, 2007;Fang et al, 2019;Fröhlich-Nowoisky et al, 2014;Gonzalez-Martin et al, 2018). Sanger sequencing-based bioaerosol analysis is being gradually replaced by the modern next-generation sequencing (NGS) (Fröhlich-Nowoisky et al, 2016) due to its high efficiency and lower cost.…”
Section: Culture-independent Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR is used to amplify the DNA region of interest prior to the traditional Sanger sequencing. Many bioaerosol studies use Sanger sequencing to identify an organism in terms of its individual genera/species by comparing its DNA with sequences available on online databases, such as the National Center for Biotechnology Information (NCBI) (Després et al, 2007;Fang et al, 2019;Fröhlich-Nowoisky et al, 2014;Gonzalez-Martin et al, 2018). Sanger sequencing-based bioaerosol analysis is being gradually replaced by the modern next-generation sequencing (NGS) (Fröhlich-Nowoisky et al, 2016) due to its high efficiency and lower cost.…”
Section: Culture-independent Methodsmentioning
confidence: 99%
“…Viruses are among the smallest bioaerosols, with a diameter up to 20 nm (Duan, 2006). Although they may be more easily suspended in the atmosphere due to their smaller size and potential attachment to finer sized PM (Gonzalez-Martin et al, 2018), they are also quite sensitive to adverse conditions during transport, e.g., UV radiation (Tseng and Li, 2005;Walker and Ko, 2007) and ozone (Tseng and Li, 2006), which could inactivate the viral particles. It has been reported that virus-containing aerosols are formed in sprays from water surfaces (Aller et al, 2005).…”
Section: Bioaerosol Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…These viruses are found in the gastrointestinal or respiratory tract where they primarily replicate, and could spread either via faecal-oral route or respiratory transmissions by droplets and aerosols (Baggen et al, 2018). Previous studies have found significantly higher positive rate for enterovirus from throat swabs (90%) compared to rectal swabs (32%), and airborne routes of transmission for enterovirus have also been reported (Chang et al, 1999;Couch et al, 1970;Gonzalez-Martin et al, 2018). On this basis, we collected data from Taiwan National Infectious Disease Statistics System, an open online database for updated information on notifiable infectious disease in Taiwan, to compare trends of infectious diseases in 2020 to the same period in 2018 and 2019, and observed significant changes for influenza and enterovirus infection (TCDC, 2020d).…”
mentioning
confidence: 99%
“…Viral detections include human adenoviruses, enteroviruses, rotaviruses and noroviruses. 56,112,117 Generally, the range of enteric pathogens identified in bioaerosols in urban settings is small and we see an even smaller range represented among the culturable targets across studies.…”
Section: Enteric Pathogensmentioning
confidence: 88%